Strategic Priorities of States in the Black Sea Region - SHARYI, Viacheslav I.; SAMOILENKO, Larysa Ya.; OVCHARENKO, Angelyka O. (Journal of Advanced Research in Law and Economics; Vol 10 No 6 (2019): JARLE Volume X Issue 6(44) Fall 2019, 2019)
The article is devoted to the research of strategic priorities of trade and economic cooperation development of the Black Sea region states. The authors argued that the formation of a common economic space in the Black Sea region is hampered due to the following factors: the similar structure of key commodities of the agricultural sector; the established practice of bilateral trade and economic relations predominance; the consequences of the global financial and economic crisis; mutual distrust among the countries in the region, that rooted in history. The energy development of the Black Sea region is experiencing global and significant qualitative changes for the better. At the same time, global factors generating instability in the Black Sea region still exist. Balance shift in the relationship between the global powers; persisting economic inequality; scarcity of natural resources while continuing their active use; crisis of traditional models of extensive development are the most significant.